Surgical Wound Infections in Obstetrics and Gynaecology - A Study from Rural Tertiary Care Hospital - Dr. Lakshmi Soujanya, Dr. Rathika R, Dr. Harish Babu B G, Dr. Narmadha NS,; Nazeer M J, Dr. Haja Abdul (International Journal of Innovative Research in Medical Science, 2017)
Introduction: One of the most common infections at gynaecology department is surgical site infection. The study was carried out to determine the incidence of post-operative wound infection in obstetrics and gynaecological surgeries along with the causative organisms and their susceptibility patterns. Materials and Methods: This was a prospective observational study conducted at Vinayaka missions medical college and hospital during August 2016-October 2017. Wound swabs were collected aseptically from post-operative wound infections and microbiological examination was performed as per standard protocol. Results: A total of 230 surgeries were included in the study. 21 specimens collected from post-operative wounds were shown bacterial growth and the incidence of post-operative wound infection was found to be 9.13%. Post-operative wound infection rate was high in swabs collected from emergency LSCS wounds7 (3.04%). Stahylococcus aureus (31.03%) was the predominant bacteria isolated. Majority of the Gram positive and Gram negative bacteria were susceptible to antibiotics such as amikacin,augmentin,cefeperazone/sulbactum, piperacillin/tazobactum. All Gram positive cocci and Gram negative bacilli were susceptible to linezolide and imipenam respectively. Conclusion: In the present study, post-operative wound infection rate was found to be 9.13%. Post-operative wound infection rate was high in swabs collected from emergency LSCS wounds7 (3.04%). Stahylococcus aureus was the predominant bacteria isolated. All Gram positive cocci and Gram negative bacilli were susceptible to linezolide and imipenam respectively. Local surveillance efforts are imperative to provide surgeons with information for choosing empirical or directed therapy.